2014
DOI: 10.1021/es5002874
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Root-Induced Mobilization of Zinc on Stable Zn Isotope Variation in the Soil–Plant System

Abstract: Stable Zn isotopes are increasingly used to trace the source of metal pollution in the environment and to gain a better understanding of the biogeochemical cycle of Zn. In this work, we investigated the effect of plants on Zn isotope fractionation in the soil-plant system of the surface horizon of two Zn-rich Technosols (pH 6.73-7.51, total Zn concentration = 9470-56600 mg kg(-1)). In a column experiment, the presence of Agrostis capillaris L. significantly increased the mobilization of Zn from soil to leachat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 64 publications
2
43
0
2
Order By: Relevance
“…With organic matter, there is a preferential retention of heavy Zn isotopes on phenolic sites of purified humic acids (Jouvin et al, 2009), which is also confirmed for surface complexation onto the organic coating of diatom cell walls (Gélabert et al, 2006) or bacteria (Kafantaris and Borrok, 2014). Zinc mobilization by plant roots or root exudates preferentially releases heavy Zn isotopes (Smolders et al, 2013;Houben et al, 2014). Within the plant, heavy Zn isotopes sorb onto the root surface, and light Zn isotopes are preferentially transported into aerial plant parts (Arnold et al, 2010;Aucour et al, 2011;Jouvin et al, 2012;Moynier et al, 2009;Weiss et al, 2005;Viers et al, 2007Viers et al, , 2015Couder et al, 2015;Tang et al, 2016;Caldelas and Weiss, 2017).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…With organic matter, there is a preferential retention of heavy Zn isotopes on phenolic sites of purified humic acids (Jouvin et al, 2009), which is also confirmed for surface complexation onto the organic coating of diatom cell walls (Gélabert et al, 2006) or bacteria (Kafantaris and Borrok, 2014). Zinc mobilization by plant roots or root exudates preferentially releases heavy Zn isotopes (Smolders et al, 2013;Houben et al, 2014). Within the plant, heavy Zn isotopes sorb onto the root surface, and light Zn isotopes are preferentially transported into aerial plant parts (Arnold et al, 2010;Aucour et al, 2011;Jouvin et al, 2012;Moynier et al, 2009;Weiss et al, 2005;Viers et al, 2007Viers et al, , 2015Couder et al, 2015;Tang et al, 2016;Caldelas and Weiss, 2017).…”
Section: Introductionmentioning
confidence: 83%
“…Additionally, the release of dissolved organic compounds, especially in rewetting periods (Fenner et al, 2001), was also found to favour the leaching of Zn through the formation of soluble metal-organic complexes (Kalbitz and Wennrich, 1998;Houben et al, 2013). Soil acidification and complexation with organic ligands mobilize preferentially heavy Zn isotopes (Houben et al, 2014;Balistrieri et al, 2008;Markovic et al, 2017;Fujii et al, 2014;Moynier et al, 2017). As a result, Zn leaching likely contributes to the Zn loss from HA-H soils and to the relative enrichment in light Zn isotopes in these organic-rich soils (Fig.…”
Section: Contribution From Organic Matter To the Zn Isotope Variationmentioning
confidence: 97%
“…It is generally accepted that the uptake of Zn from soil has at least four main mechanisms (see also Aucour et al, 2011;Caldelas et al, 2011;Houben et al, 2014;Jouvin et al, 2012;Tang et al, 2012 and references herein): (1) root-induced soil acidification and mobilization of soil Zn (Houben et al, 2014;Loosemore et al, 2004); (2) Zn adsorption on root cell wall (Hall, 2002); (3) non-specific Zn transfer through the plasma membrane into the root symplast via low-affinity transporters (Hacisalihoglu et al, 2001), or (4) Zn specific uptake by either ZIP proteins or phytosiderophores released by the plant roots to transfer the Fe/Zn complexes through the membrane (Claus et al, 2013). The present growth media are far from the Fe-or Zn-deficiency conditions, hence the release of siderophores by L. multiflorum roots was probably negligible (Rö mheld and Marschner, 1990).…”
Section: Species Differences In Zn Uptake Translocation and Isotope mentioning
confidence: 99%
“…The understanding of the Zn transfer processes between soils and plants should help us to fully assess the effects of anthropogenic activities on the metal cycling in the Earth's critical zone. Recent improvements in MC-ICP-MS (multiple collector inductively coupled plasma mass spectrometry) allow obtaining highly precise and accurate data for nontraditional stable zinc isotope compositions in plants and soils (e.g., Arnold et al, 2010aArnold et al, ,b, 2015Houben et al, 2014;Jouvin et al, 2009Jouvin et al, , 2012Moynier et al, 2009;Smolders et al, 2013;Tang et al, 2012;Viers et al, 2007;von Blanckenburg et al, 2009;Weiss et al, 2005). Zinc isotopes can be used as powerful tools for a better understanding of the mechanisms of Zn uptake, transport, storage, and tolerance by plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation